Analysis of The Influence of Social Ecological Factors on Access To Health Services By Women Giving Birth In Kupang Regency: Cross-Sectional Study - Abuk Seran, Agustina; Isabela Tabelak, Tirza Vivianri; Marasabessy, Nur Baharia; Lestaluhu, Viqy; Meriaty Huru, Matje; Boimau, Adriana M.S (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
Background: The socio-ecological model describes how women's access to health services is influenced at various levels, including the individual, interpersonal, community, organizational, and policy levels.Objective: to analyze The Influence of social ecological factors on access to health services by women giving birth in Kupang RegencyMethods: correlation analytical research, with a cross-sectional design. The sampling technique used was purposive sampling for 1 month, which obtained up to 112 samples. This research was carried out at Kupang Regency. The independent variable was socioeconomic position, education level, residence, age, employment status, and belief, and the dependent variable was access to health services. Data were collected using the instruments in this study are the Emotional Belief Questionnaire (EBQ) The overall Cronbach’s alpha for the (EBQ) scale was 0.84. Statistical test using the Chi-Square test.Results: socioeconomic(p-value=.000), education level (p-value=.000), Residence (p-value=.000), age (p-value=.000), work status (p-value=.000), and anxiety (p-value=.000). There is a significant related between socioeconomic position, education level, location, age, employment status, and belief in access to health services. Conclusion: Socioeconomic status, level of education, residence, age, employment status, and beliefs all affect a woman's ability to get health care during childbirth.